Light and acoustic pulse interaction in the Bragg diffraction region - BODZENTA, Jerzy; KLESZCZEWSKI, Zygmunt (Archives of Acoustics, 1989)
This paper presents results of a theoretical analysis of interactions between a mono-chromatic light wave and series of acoustic pulses in the Bragg diffraction region. An expression for the electric field intensity of a diffracted light wave was achieved on the basis of known theories. The intensity is a sum of harmonics formed due to the diffraction of inciding light onto harmonics of the acoustic wave. Individual components of the light wave resulting from diffraction are spatially separated. A numeric analysis performed for a series of perfect, rectangular acoustic pulses proved that the measurement of the angular distribution of light intensity in a diffracted beam leads to the analysis of the acoustic wave's amplitudes spectrum. Therefore, an acoustic wave spectrum analyzer can be built with the utilization of the described interaction. The possibility of measuring parameters of acoustic pulses directly during propagation in the medium without influencing these parameters is the main advantage of such an analyzer. The frequency band of the proposed analyzer is limited by the Bragg condition depends on acoustic and acousto-optics properties of the medium and the geometry of the interaction region.